Pengaruh Senam Dismenore Dan Kompres Hangat Terhadap Penurunan Nyeri Haid (Dismenore) Pada Remaja Putri Di Sma N 1 Sorkam Barat - Nuraisyah Hutagalung; Trisno Susilo; Yeni Vera (Jurnal Kesehatan dan Fisioterapi, 2022)
Dysmenorrhea is a menstrual disorder in the form of pain or severe pain in the lower abdomen caused by the activity of prostaglandins, where during menstruation the damaged uterine lining is removed and replaced by new compounds called prostaglandins. This prostaglandin compound causes the uterine muscles to contract. In general, uterine muscle contractions are not felt, but the contractions are severe and often cause blood flow to the uterus to be disrupted, causing pain so that it can temporarily interfere with activities. Dysmenorrhea can be treated with non-pharmacological therapy in the form of dysmenorrhea gymnastics and warm compresses to reduce the pain level of dysmenorrhea. The purpose of this study was to examine the effect of dysmenorrhea exercise and warm compresses in reducing the level of dysmenorrhea pain. Methods: This research design uses a quasi experiment with two groups pre-post test with sampling using purposive sampling technique with the same total of 23 respondents in each group and using the Wilcoxson Signed Rank test with a p value of 0.000 (p <0.005) . Research results: The results of this study indicate that the results of statistical tests using the Wilcoxson Signed Rank test. Dysmenorrhea exercise test in group 1 with p value = 0.000 and warm compresses in group 2 with p value = 0.000. Conclusion: It can be seen that dysmenorrhea exercise and warm compresses can reduce the pain scale of dysmenorrhea. Both of these interventions are equally effective in reducing the pain scale of dysmenorrhea. Therefore, researchers recommend using one or both of these interventions to reduce dysmenorrhea pain. Keywords: Dysmenorrhea, Dysmenorrhea Gymnastics, Warm Compress